An experimental investigation of the impact of retrofitting an underwater stern foil on the resistance and motion. (1st June 2020) - Hou, Hongbo; Krajewski, Mateusz; Ilter, Y. Kaan; Day, Sandy; Atlar, Mehmet; Shi, Weichao
Abstract: Due to growing concerns about the environment and increasing prices in fuel, Energy Saving Device are becoming more and more important for ship. Hull Vane is an Energy Saving Device that can be retrofitted to the existing vessels or designed to new builds. This paper investigates the effect of retrofit to reduce the ship resistance and to improve the motion response in still water and sea states based on experimental tests. After the Hull Vane with Rhodes St. Gense 32 profile is designed and applied on a model DTMB 5415 hull in 1:51 scale with different attack angles and locations, the various experiments are conducted in the Kelvin Hydrodynamics Laboratory, University of Strathclyde. The model test shows Hull Vane can reduce and smoothen the stern wake markedly and significantly reduce the total resistance of ship. Pitch and heave motion of ship can be reduced by Hull Vane, because of which the comfort and operability of ship can be improved. Highlights: An energy saving device, underwater stern foil, is applied on a displacement ship model to drag reduction. Performance in calm sea and in waves has been investigated in the towing tank. Two full-scale extrapolation methods are proposed and implemented to predict the performance in full-scale applications. In the experiment, Hull Vane provides resistance reduction with maximum of 3.8% and 5.5% in still water and waves. Performance in waves with the hull vane can be improved both in terms of the resistance and the motion response.